Quantitative Analysis of Ceftriaxone Sodium in Parenteral Dosage Form - A. Alothman, Zeid; Raza Siddiqui, Masoom; Ali Khan, Moonis (Asian Journal of Chemistry, 2013)
Simple and sensitive kinetic spectrophotometric methods are described for the determination of ceftriaxone sodium in its pure form and parenteral dosage from. The kinetic method is based on spectrophotometric studies of the oxidation of ceftraixone with sodium permanganate in basic medium. Parameters affecting the colour developments are examined and optimized. The developed analytical procedure was validated for its linearity, range, accuracy and precision, limit of detection and limit of quantitation. The calibration curves were linear over the range of 5-45 μg mL-1. The limit of detection and limit of quantitation of the initial rate and fixed time method was found out to be 0.128, 0.558, 0.387 and 1.78, respectively. The possible mechanism of the reaction is also proposed.